Bacteriomic Analyses of Asian Citrus Psyllid and Citrus Samples Infected With “Candidatus Liberibacter asiaticus” in Southern California and Huanglongbing Management Implications - Huang, Jiaquan; Dai, Zehan; Zheng, Zheng; da Silvia, Priscila A.; Kumagai, Luci; Xiang, Qijun; Chen, Jianchi; Deng, Xiaoling (Frontiers in Microbiology, 2021)
Citrus Huanglongbing (HLB, yellow shoot disease) is associated with an unculturable α-proteobacterium ‘Candidatus. Liberibacter asiaticus’ (CLas). HLB was found in southern California in 2012 and the current management strategy is based on suppression of the Asian citrus psyllid (ACP, Diaphorina citri) that transmits CLas and removal of confirmed CLas-positive trees. Little is known about ACP-associated bacteria (AABacts) and citrus-associated bacteria (CABacts) in the HLB system. Such information is important in HLB management, particularly for accurate detection of CLas. Recent advancements in next generation sequencing (NGS) technology provide new opportunities to study HLB through genomic DNA sequence analyses (metagenomics). In this study, HLB-related AABacts and CABacts in ACP and citrus (represented by leaf midrib tissues) samples from southern California were analyzed. A metagenomic pipeline was developed to serve as a prototype for future bacteriomic research. This pipeline included steps of NGS in Illumina platform, de novo assembling of Illumina reads, sequence classification using Kaiju tool, acquisition of bacterial draft genome sequences, and taxonomic validation and diversity evaluation using average nucleotide identity (ANI). The identified AABacts and CABacts included: Bradyrhizobium, Buchnera, Burkholderia, ‘Candidatus. Profftella armature’, ‘Ca. Carsonella ruddii’, CLas, Mesorhizobium, Paraburkholderia, Pseudomonas, and Wolbachia. The whole genome of a CLas strain recently found in San Bernardino County was sequenced and classified into PTG-1 group, one of the five known CLas groups in California. Based on sequence similarity, Bradyrhizobium and Mesorhizobium were identified as possible source that could interfere with CLas detection using the16S rRNA gene-based HLBas-PCR commonly used for HLB diagnosis, particularly at low or zero CLas titer situation.